The Effect Of Sls (Sodium Lauryl Sulphate) On The Formulation Of Lime (Citrus Aurantifolia) Essential Oil Hand Soap - Definingsih Yuliastuti; Silva Galeh Pramudita; Dessy Ratna Sari (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2026)
Liquid soap is currently the most popular soap product, due to its attractive and practical form. Soap is often enriched with several additives, such as surfactants, to improve its quality. The most common surfactant is SLS (Sodium Lauryl Sulphate), as it can reduce skin irritation and has excellent foaming properties. Adding too much SLS can cause irritation and dry skin. Hand soap can be formulated with natural active ingredients, such as lime peel essential oil, which contains antibacterial properties. This study was conducted by creating soap preparations in FI, FII, and FIII. The purpose of this study was to determine the effect of varying SLS concentrations on the physical quality of hand soap preparations, including organoleptic tests, homogeneity tests, pH tests, viscosity tests, and foam height tests. The results of the study showed that the hand soap was thick, had a distinctive fresh lime odour, and was yellow in colour. The hand soap preparations for each formula were homogeneous. The pH of the three preparations ranged from 6.01 to 6.15. The viscosity of the three preparations ranged from 805 to 846.33 cPs. The foam height of the three formulas ranged from 48 to 55 mm. Data analysis in this study used a one-way ANOVA test. The conclusion of this study is that variations in SLS concentration affect the organoleptic test results, pH, viscosity, and foam height, but do not affect the homogeneity test results.